Increasing the Productivity and Independence of Ex-People with Mental Disorders (ODGJ) Through Life Skills Based Empowerment: Peningkatan Produktivitas dan Kemandirian Ex-Orang Dengan Gangguan Jiwa (ODGJ) Melalui Pemberdayaan Berbasis Life Skill - Cahaya, Noor; Wathan , Nashrul; Kaidah, Siti (Universitas Lancang Kuning, 2024)
People with mental disorders experience disturbances in thoughts, feelings, and behaviors that cause them to experience decreased productivity and personal autonomy. The program was aimed at increasing the productivity and personal autonomy of ex-ODGJ through life skills-based training in the form of making handicrafts. The target of the program were ex-ODGJs who were undergoing the rehabilitation process at the Rumah Singgah